Are Fusion Transcripts in Relapsed/Metastatic Head and Neck Cancer Patients Predictive of Response to Anti-EGFR Therapies?. (12th November 2017) - Bossi, Paolo; Siano, Marco; Bergamini, Cristiana; Cossu Rocca, Maria; Sponghini, Andrea P.; Giannoccaro, Marco; Tonella, Luca; Paoli, Alessandro; Marchesi, Edoardo; Perrone, Federica; Pilotti, Silvana; Locati, Laura D.; et al.
Abstract : Prediction of benefit from combined chemotherapy and the antiepidermal growth factor receptor cetuximab is a not yet solved question in head and neck squamous cell carcinoma (HNSCC). In a selected series of 14 long progression-free survival (PFS) and 26 short PFS patients by whole gene and microRNA expression analysis, we developed a model potentially predictive of cetuximab sensitivity. To better decipher the "omics" profile of our patients, we detected transcript fusions by RNA-seq through a Pan-Cancer panel targeting 1385 cancer genes. Twenty-seven different fusion transcripts, involving mRNA and long noncoding RNA (lncRNA), were identified. The majority of fusions (81%) were intrachromosomal, and 24 patients (60%) harbor at least one of them. The presence/absence of fusions and the presence of more than one fusion were not related to outcome, while the lncRNA-containing fusions resulted enriched in long PFS patients (P = 0.0027 ). The CD274-PDCD1LG2 fusion was present in 7/14 short PFS patients harboring fusions and was absent in long PFS patients (P = 0.0188 ). Among the short PFS patients, those harboring this fusion had the worst outcome (P = 0.0172 ) and increased K-RAS activation (P = 0.00147 ). The associations between HNSCC patient's outcome following cetuximab treatment and lncRNA-containing fusions or the CD274-PDCD1LG2 fusion deserve validation in prospective clinical trials.